2015
DOI: 10.1111/cp.12047
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and behaviour problems in children with Autism Spectrum Disorders: The mediating role of parent mental health

Abstract: Key words autism spectrum disorder, child problem behaviours, family functioning, parent mental health, parent stress. Correspondence Rachel Jellett, AbstractBackground: Parents of young children with Autism Spectrum Disorders (ASDs) are often relied on to help implement therapy with their child, which occurs within a family context. Therefore, it is important to understand and support families where there is a child with an ASD. Although individual parent factors have received substantial research attention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…In particular balanced levels of cohesion which tended towards a deep engagement among family members was positively associated with behaviors finalized to companionship and cooperation. Although unbalanced levels of cohesion and flexibility characterize more frequently families with a child with ASD than families having only TD children (Baker et al 2011;Gau et al 2012;Jellett et al 2015;Higgins et al 2005; Manor-Binyamini 2011), family satisfaction levels are more likely to have a more determinant role in family functioning when a member has a disability. In particular, a recent study (Pruitt et al 2016) demonstrated that when balanced levels of family satisfaction are reported by family members, increased daily positive parenting interactions between mother and their children with ASD are observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular balanced levels of cohesion which tended towards a deep engagement among family members was positively associated with behaviors finalized to companionship and cooperation. Although unbalanced levels of cohesion and flexibility characterize more frequently families with a child with ASD than families having only TD children (Baker et al 2011;Gau et al 2012;Jellett et al 2015;Higgins et al 2005; Manor-Binyamini 2011), family satisfaction levels are more likely to have a more determinant role in family functioning when a member has a disability. In particular, a recent study (Pruitt et al 2016) demonstrated that when balanced levels of family satisfaction are reported by family members, increased daily positive parenting interactions between mother and their children with ASD are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence, confirmed by cross-culture studies (Gau et al 2012;Manor-Binyamini 2011), has shown that families having a child with ASD report less affective family functioning, in terms of both flexibility and cohesion (Baker et al 2011;Higgins et al 2005). Furthermore, greater severity of behavior problems of children with ASD and parent mental psychopathology seem to negatively impact on family functioning (Jellett et al 2015;Pruitt et al 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Although the experience of parenting any child can be stressful, parents caring for a disabled child experience a greater level of stress (Hayes & Watson, 2013) or have poorer perceived health than other parents (Brehaut et al, 2011). Moreover, behavioural challenges presented by the care recipient, (Jellett, Wood, Giallo, & Seymour, 2015;Plant & Sanders, 2007) ineffective coping strategies, poor family functioning, and poor social support have been associated with the parental caregiver burden in previous studies (Raina et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The parent-child dysfunctional interaction, which is caused by the children's problematic behavior, although it brings about negative effects in the family system, such as parents' increased stress and fatigue, does not necessarily reduce the functionality of the family (Jellet et al, 2014). The significance of the classification of Zhou and Yi (2014) may be supported and specifically the distinction of group Δ of parents, who are usually the ones that give up trying to educate and take care of their children, when they lose their hopes for the improvement of the situation and their motives for participation in any management of the autistic child are reduced.…”
Section: Discussionmentioning
confidence: 99%